2017
DOI: 10.1002/ets2.12130
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Uses of GRE® Scores After the Launch of the GRE® revised General Test in August 2011

Abstract: This survey study investigated how graduate school admissions committees perceive and use the GRE® General Test and GRE® Subject Tests after the launch of the GRE® revised General Test in August 2011. These perceptions and uses impact the validity of the tests. Prior research about the perceptions and uses of the General Test and Subject Tests was last conducted in 2002 and, prior to that, in 2000 (for writing) and 1984. Therefore, even without test revisions, perceptions and uses of the GRE tests may have cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…There have been studies conducted on how students perceive the GRE and whether it is viewed as being a fair test by different social classes and ethical groups. Research conducted by Klieger et al in 2017 concluded that for United States citizens, "the average standardized test scores of White and Asian examinees have generally exceeded the average scores of Black and Hispanic examinees by at least one half to a full standard deviation [5]." This seems to support the claim made by Groeger in 1998 who indicated that a "sample of 4,248 first-year graduate students showed that 96% of the Black applicants indicated that these tests are oriented toward the White middle-class culture [6]."…”
Section: Perceptions Of the Grementioning
confidence: 99%
See 3 more Smart Citations
“…There have been studies conducted on how students perceive the GRE and whether it is viewed as being a fair test by different social classes and ethical groups. Research conducted by Klieger et al in 2017 concluded that for United States citizens, "the average standardized test scores of White and Asian examinees have generally exceeded the average scores of Black and Hispanic examinees by at least one half to a full standard deviation [5]." This seems to support the claim made by Groeger in 1998 who indicated that a "sample of 4,248 first-year graduate students showed that 96% of the Black applicants indicated that these tests are oriented toward the White middle-class culture [6]."…”
Section: Perceptions Of the Grementioning
confidence: 99%
“…A study conducted by Klieger et al in 2017 sent out a survey with several questions regarding the use of the GRE in the admissions process for multiple areas of study including the Science-Technology-Engineering-Mathematics (STEM) field, as well as the social sciences, arts, and humanities fields. From the responses, "72% of respondents indicated the GRE revised General Test is required for all candidates, 18% said it is required, but could be waived in some circumstances, 4% said it is required or recommended for some applicants, 1% said it is recommended for all applicants, fewer than 1% said it is neither required nor recommended but would be considered if submitted, and 5% said it is not used at all [5]." The respondents from the STEM field indicated that 80% required the GRE General Test which was the highest of the three different areas of study [5].…”
Section: Graduate Schools Admissions Using the Gre Scoresmentioning
confidence: 99%
See 2 more Smart Citations
“…Since its inception, the GRE General has undergone several additions, including a significant revision in 2011 (Klieger et al, 2017). Presently, the GRE General measures Verbal Reasoning (section GRE-V), Quantitative Reasoning (section GRE-Q), and Analytical Writing (section GRE-A).…”
Section: The Gre Structurementioning
confidence: 99%